(House)lights out: encounters with darkness and compositions of going dark. Issue 3 (2nd October 2022) - Shyldkrot, Yaron
ABSTRACT: This article examines encounters with darkness through compositions of houselights and their elimination, arguing that not all brushes with darkness are alike. While eradicating houselights directs seeing and focuses attention, which already implies a dramaturgical-compositional significance, the design of light in the auditorium is predominantly relegated to a preshow preamble that will quickly be switched off. In response, I propose that houselights play an integral part in the performance event and carry a richer dramaturgical and scenographic role than is normally assigned to them. In a related move, within the growing study of theatrical darkness, the verb 'to plunge' has been embraced to refer to the immersion of audiences in darkness. However, the recurring use of the term obscures the many ways through which audiences are invited into darkness. Expanding the formulation of the plunge, this article traces the potential embedded in different encounters with darkness, paying close attention to the affective experiences of the juncture of light and darkness. Turning to theatre in the dark, I examine how (house)light is eliminated and darkness emerges in David Rosenberg and Glen Neath's Fiction (2015), Fye and Foul's Cathedral (2016) and my performance of Campfire (2016). I do so through a move between toning and tuning, suggesting how akin to the compositions of lighting on stage, designing lights in the auditorium and the course of powering them off can impact the sense- and meaning-making in/of the performance, setting the tone and attuning audiences to what is about to unfold.